Intercultural Communicative Competence in English Teaching and Learning for Islamic Universities: Students Perceptions and Expectations - Noviyanti, Sarid Dewi (JALL (Journal of Applied Linguistics and Literacy), 2024)
This research delves into the realm of intercultural communicative competence within the context of English teaching and learning, specifically focusing on Islamic universities. The study centers on the perceptions and expectations of students regarding this competence. By exploring the intersection of language, culture, and education, the research aims to provide insights into how students enrolled in Islamic universities conceptualize intercultural communicative competence as part of their English language education. Through a qualitative approach, the study analyzes students' perspectives from three Islamic universities to uncover their attitudes, beliefs, and anticipated outcomes related to intercultural communication in an academic setting. The findings hold implications for curriculum development, pedagogical approaches, and the enhancement of cross-cultural understanding within English language programs at Islamic universities.